2008
DOI: 10.1007/s11010-008-9717-5
|View full text |Cite
|
Sign up to set email alerts
|

Remote renal preconditioning-induced cardioprotection: a key role of hypoxia inducible factor-prolyl 4-hydroxylases

Abstract: Remote preconditioning is a unique phenomenon in which brief episodes of ischemia and reperfusion to remote organ protect the target organ against sustained ischemia-reperfusion (I/R)-induced injury. Protective effects of remote renal preconditioning (RRPC) are well established in heart, but their mechanisms still remain to be elucidated. So, the present study was designed to investigate the possible role of oxygen-sensing hypoxia inducible factor-prolyl 4-hydroxylases (HIF-P4Hs) in RRPC-induced cardioprotecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…Other investigators demonstrated that preconditioning at a remote organ such as renal ischemia-reperfusion can also induce cardioprotection [35] . Interestingly, a recent study suggested a role for HIF-1 activation in the remote renal preconditioning of rat hearts, since the authors were able to abolish the remote preconditioning by a putative activator of PHDs, alpha-ketoglutarate (200 mg/kg, ip) [36] . On the other hand, a few conflicting results have been published on the role of HIF-1α in ischemic preconditioning.…”
Section: Involvement Of Hif-1 In Ischemic Preconditioning and Post Comentioning
confidence: 99%
“…Other investigators demonstrated that preconditioning at a remote organ such as renal ischemia-reperfusion can also induce cardioprotection [35] . Interestingly, a recent study suggested a role for HIF-1 activation in the remote renal preconditioning of rat hearts, since the authors were able to abolish the remote preconditioning by a putative activator of PHDs, alpha-ketoglutarate (200 mg/kg, ip) [36] . On the other hand, a few conflicting results have been published on the role of HIF-1α in ischemic preconditioning.…”
Section: Involvement Of Hif-1 In Ischemic Preconditioning and Post Comentioning
confidence: 99%
“…For example, remote ischemic preconditioning (remote IPC) is a powerful innate mechanism which prevents lethal ischemic injury by prior sub-lethal ischemia at an anatomically distant site [1] and has been exploited in a number of clinical settings [2]. Remote IPC and its associated applications may rely upon release of endocrine factors from ischemic cells that initiate adaptive gene programs in recipient tissue [3], and a number of these factors may be directly regulated by the master transcription factor of hypoxia, HIF-α [46]. However, the full complement of such HIF-dependent molecular effectors remains undefined.…”
Section: Introductionmentioning
confidence: 99%
“…The infarct size was expressed as percentage of total left ventricular volume (% LVV) and total left ventricular weight (% LVW) respectively. [15][16][17] Estimation of Lactate Dehydrogenase (LDH) LDH was estimated in samples of coronary effluent collected after stabilization (basal), immediately and 30 min after reperfusion using 2,4-DNPH method as described by King.…”
Section: Methodsmentioning
confidence: 99%